2022
DOI: 10.3390/ma15134549
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent Circuit Models: An Effective Tool to Simulate Electric/Dielectric Properties of Ores—An Example Using Granite

Abstract: The equivalent circuit model is widely used in high-voltage (HV) engineering to simulate the behavior of HV applications for insulation/dielectric materials. In this study, equivalent circuit models were prepared in order to represent the electric and dielectric properties of minerals and voids in a granite rock sample. The HV electric-pulse application shows a good possibility of achieving a high energy efficiency with the size reduction and selective liberation of minerals from rocks. The electric and dielec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Fukushima et al [ 6 , 7 ] reported their studies on the modeling and simulation of electrical disintegration. Fukushima et al [ 6 ] developed a simulation method using equivalent circuits of granite to better understand the crushing process with high-voltage (HV) electrical pulses that have been previously identified as a selective liberation method.…”
Section: The Special Issuementioning
confidence: 99%
See 2 more Smart Citations
“…Fukushima et al [ 6 , 7 ] reported their studies on the modeling and simulation of electrical disintegration. Fukushima et al [ 6 ] developed a simulation method using equivalent circuits of granite to better understand the crushing process with high-voltage (HV) electrical pulses that have been previously identified as a selective liberation method.…”
Section: The Special Issuementioning
confidence: 99%
“…Their results suggested that the void volume in each mineral is important in calculating the electrical properties and confirmed that considering both the electrical conductivity and dielectric constant of granite can more accurately represent the electrical properties of granite under HV electric pulse application. Fukushima et al [ 7 ] prepared equivalent circuit models in order to represent the electric and dielectric properties of minerals and voids in a granite rock sample, considering HV electrical pulse application. Using the electric and dielectric properties and the mineral compositions measured, they prepared ten patterns of equivalent circuit models.…”
Section: The Special Issuementioning
confidence: 99%
See 1 more Smart Citation